Do Resources Aid in Supply Chain Functioning and Management? Yes, But More (and More Precise) Research is Needed. Issue 3 (July 2014) - Crook, T. Russell; Esper, Terry L.
<x xml:space="preserve">Abstract</x> We highlight key contributions from the special topic forum (STF) articles and detail findings from a survey of researchers interested in the role of resources on supply chain functioning and management. We assert that the STF articles have closed important gaps between what needed to be known and is now known about how and when resources aid supply chains. However, the survey findings suggest that researchers who invoke theories of resources need to be more precise in their theoretical exposition and that future research needs to focus more heavily on the role of resources not just within, but also beyond a firm's boundaries (i.e., interfirm), and how those resources aid supply chains. The survey findings also suggest that future supply chain studies should focus more on investigating contingency relationships, and "fitting" research designs to address the specific research question of interest. Broadly speaking, we conclude that resources within and across firm boundaries are vital to supply chain functioning and management, but that as research evolves, new insights might be best characterized by studies that take stock of critical contingencies.